siRNA-mediated mesothelin silencing for treatment of mesothelioma - Aksoy, A.; Varoglu, A.; Onalan, E. E.; Tektemur, A.; Artas, G. (Funpec-Editora, 2022)
It is known that mesothelin (MSLN) is overexpressed in some cancers, and that it plays a role in cell growth through Wnt family member 1 protein. Malignant transformation usually occurs with disruption of autoregulation of autophagy-related genes. We examined the effect of MSLN on survival and clinicopathological features in mesothelioma cases, as well as variations in genes associated with autophagy, invasion, apoptosis-related genes after siRNA-mediated MSLN silencing transfection in a mesothelioma cell line (SPC212). MSLN expression was analyzed, immunohistochemically, in formalin-fixed paraffin-embedded 60 mesothelioma cases. MSLN expression was categorized by median MSLN histoscores as low (L), high (H). The correlation between the levels of MSLN expression, clinicopathological features, and survival was determined in mesothelioma cases. The siRNA-mediated MSLN incubated SPC212 cells were transfected and compared to negative control siRNAs. mRNA levels were determined for autophagy, invasion, and apoptosis related-genes with RT-PCR, and western blotting in SPC212 cells after MSLN silencing. All of the cases were immunoreactive for MSLN expression. H-MSLN was associated with a favorable prognosis according to Kaplan-Meier survival analysis, but Cox regression analysis revealed that only stage was a significant independent factor for estimating survival. MSLN overexpression was significantly higher in early-stage, mesothelioma cases without nodal involvement. Significant silencing in MSLN was found (87.5%) after siRNA applications. Apoptosis and autophagy were upregulated by increasing apoptosis-related genes, BAK1, BAX, CASP1-7, and autophagy-related genes, ATG2, ATG16L1. Cell proliferation was knocked down predominantly by inhibiting the invasion-related genes, MMP1, 10, 11, 13, in SPC212 cell lines. MSLN silencing was determined to significantly increase CASP3, but did not change LC3 in western blotting, respectively. In conclusion, siRNA-mediated silencing MSLN can promote apoptosis, autophagy, and also partially inhibit proliferation. We suggest that MSLN can serve as a potential therapeutic target in mesothehoma.
Keywords: Autophagy; Apoptosis; Mesothelioma; Mesothelin; Proliferation; Survival